Lesbian and bisexual women's gynaecological conditions: a systematic review and exploratory meta‐analysis. (15th November 2016) - Robinson, K; Galloway, KY; Bewley, S; Meads, C
Abstract : Background: Little is known about the gynaecological health of lesbian and bisexual (LB) women. Objectives: To examine differences in incidence and/or prevalence of gynaecological conditions in LB compared with heterosexual women. Search strategy: The systematic review protocol was prospectively registered (PROSPERO‐CRD42015027091) and searches conducted in seven databases. Selection criteria: Comparative studies published 2000–2015, reporting any benign (non‐infectious) and/or malignant gynaecological conditions with no language or setting restrictions. Data collection and analysis: Inclusions, data extraction and quality assessment were conducted in duplicate. Meta‐analyses of condition prevalence rates were conducted where ≥3 studies reported results. Main results: From 567 records, 47 full papers were examined and 11 studies of mixed designs included. No studies directly addressing the question were found. Two chronic pelvic pain studies reported higher rates in bisexual compared with heterosexual women (38.5 versus 28.2% and 18.6 versus 6.4%). Meta‐analyses showed no statistically significant differences in polycystic ovarian syndrome, endometriosis and fibroids. There was a higher rate of cervical cancer in bisexual than heterosexual women [odds ratio (OR) = 1.94; 95% CI 1.46–2.59] but no difference overall (OR = 0.76; 95% CI 0.15–3.92). There was a lower rate of uterine cancer in lesbian than heterosexual women (OR = 0.28; 95% CI 0.11–0.73) and overall (OR = 0.36; 95% CI 0.13–0.97), but no difference in bisexual women (OR = 0.43; 95% CI 0.06–3.07). Conclusions: More bisexual women may experience chronic pelvic pain and cervical cancer than heterosexual women. There is no information on potential confounders. Better evidence is required, preferably monitoring sexual orientation in research using the existing validated measure and fully reporting results. Tweetable abstract: Lesbians have less uterine cancer than heterosexual women; bisexuals have more pelvic pain and cervical cancer. Tweetable abstract: Lesbians have less uterine cancer than heterosexual women; bisexuals have more pelvic pain and cervical cancer. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14414 .